Influence of Genetic Selection for Growth and Broodstock Diet n-3 LC-PUFA Levels on Reproductive Performance of Gilthead Seabream, Sparus aurata - Shajahan Ferosekhan; Serhat Turkmen; Cathaysa Pérez-García; Hanlin Xu; Ana Gómez; Nazeemashahul Shamna; Juan Manuel Afonso; Grethe Rosenlund; Ramón Fontanillas; Anselmo Gracia; Marisol Izquierdo; Sadasivam Kaushik (Animals, 2021)
Genetic selection in gilthead seabream (GSB), Sparus aurata, has been undertaken to improve the growth, feed efficiency, fillet quality, skeletal deformities and disease resistance, but no study is available to delineate the effect of genetic selection for growth trait on GSB reproductive performance under mass spawning condition. In this study, high growth (HG) or low growth (LG) GSB broodstock were selected to evaluate the sex steroid hormones, sperm, egg quality and reproductive performance under different feeding regime of commercial diet or experimental broodstock diet containing either fish oil (FO) or vegetable oil (VO) based diet. Under commercial diet feeding phase, broodstock selected for either high growth or low growth did not show any significant changes in the egg production per kg female whereas egg viability percentage was positively (p = 0.014) improved by the high growth trait broodstock group. The experimental diet feeding results revealed that both growth trait and dietary fatty acid composition influenced the reproductive performance of GSB broodstock. In the experimental diet feeding phase, we observed high growth trait GSB males produced a higher number of sperm cells (p < 0.001) and also showed a higher sperm motility (p = 0.048) percentage. The viable egg and larval production per spawn per kg female were significantly improved by the broodstock selected for high growth trait and fed with fish oil-based diet. This present study results signifies that gilthead seabream broodstock selected on growth trait could have positive role in improvement of sperm and egg quality to produce viable progeny.